Exploration of the effects of chloride ions on the analysis of polar compounds at low concentrations by hydrophilic interaction liquid chromatography coupled to a charged aerosol detector: Application to tromethamine. Issue 6 (15th January 2023) - Toussaint, Balthazar; Immame Hassane Beck, Taslyne; Surget, Estelle; Boudy, Vincent; Jaccoulet, Emmanuel
Abstract : In this study, we discuss the origin of the slightly increased response of the charged aerosol detector when low‐concentration polar drugs formulated with sodium chloride are analyzed by hydrophilic interaction liquid chromatography coupled to the charged aerosol detector. In the case of tromethamine mixed with saline solutions, we investigated several levels including the mobile phase, sample matrix, and detection. We show that the analysis of the rich‐salted sample results in both interactions with the mobile phase modifiers and the stationary phase during the run time. With 150 mM NaCl as a compounding solution, a slight increase in the tromethamine peak area was observed (<5.5%). Our study suggests that chloride ions in excess sequentially interact firstly with the counterions from the organic modifiers and secondly with the analyte via the stationary phase and the contribution of hydrophilic interaction liquid chromatography retention mechanisms. Because of these effects, the hydrophilic interaction liquid chromatography‐charged aerosol detector analysis of drugs in saline solutions requires particular attention, and a correction factor for quantitative purposes that accounts for formulation ions remains appropriate.